Aucassin and Nicolette : translated from the Old French - Bourdillon, Francis William, 1852-1921 (Salt Lake City, UT : Project Gutenberg, 2007)
"Aucassin and Nicolette" by Francis William Bourdillon is a lyrical narrative composed in the close of the 12th century, reflecting a medieval romance akin to both an epic poem and a novel. The story presents a timeless theme of love, focusing on the passionate yet thwarted romance between Aucassin, a young nobleman, and Nicolette, a captive lady of noble birth, exploring issues of societal class, identity, and personal desire against a backdrop of familial and political conflict. The narrative glorifies the poignant emotional struggles of Aucassin, who defies his family's wishes to pursue a bright future with Nicolette, despite her status as a slave-girl. Following their initial separation$1 (Binstigated by Aucassin's father, who hopes to prevent his son from pursuing this forbidden love$1 (Bthe lovers endure numerous trials, including imprisonment, warfare, and personal sacrifice. The story unfolds through a tapestry of verses that illuminate their unwavering devotion, culminating in a tale of perseverance as they overcome their circumstances, ultimately reuniting against overwhelming odds in a journey filled with nostalgia and hope. (This is an automatically generated summary.)s
Release date is 2007-10-28
Transcribed from the 1908 Kegan Paul, Trench, Trubner & Co. edition by David Price
Keywords: Romances -- Translations into English; Legends -- France -- Translations into English; French literature -- Translations into English